What the Public Wants to Know - Mária Žuffová (Journal of Quantitative Description: Digital Media)
Access to information (ATI) policies are perceived as serving predominantly a government oversight function, utilized by investigative journalists and activists to reveal political corruption or misconduct. In this study, I apply text-as-data methods to 37,356 information requests submitted to the UK central government through the online participation platform WhatDoTheyKnow over a decade to explore public information demand. I analyze what information citizens seek and categorize it based on the probability of specific topics within the sample of requests. Citizens use online participation platforms such as WhatDoTheyKnow because it lowers the barriers to interacting with the state, and it is often the only way to obtain information, as, based on access to information laws, bureaucracies are legally obliged to respond. In line with previous research, the findings show that submitted requests are heterogeneous. By focusing on one of the identified topics — UK Welfare Reform — I also demonstrate that information requests can serve as an indicator of public reactions to recently adopted or reformed policies. Citizens use them to share their experiences, voice concerns about how these policies impact their lives, and seek clarification.